PENGARUH KUALITAS PELAYANAN, KETEPATAN WAKTU PENGIRIMAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Pelanggan PT. Pos Indonesia) - Krisna Gusti Putra; Khairul Bahrun (Yayasan Insani Mandiri Santani, 2023)
This study aims to determine the effect of Service Quality, Timeliness of Delivery and Facilities on Customer Satisfaction of PT. Pos Indonesia (Persero) in Bengkulu City. This study uses quantitative research methods. The population in this study are the customers of PT. Pos Indonesia Kenanga Gardens, Ratu Agung District, Bengkulu City, Bengkulu, with a sampling method using the